The Adrenal Lipid Droplet is a New Site for Steroid Hormone Metabolism. Issue 23 (5th December 2018) - Yu, Jinhai; Zhang, Linqiang; Li, Yunhai; Zhu, Xiaotong; Xu, Shimeng; Zhou, Xiao‐Ming; Wang, Haizhen; Zhang, Hongchao; Liang, Bin; Liu, Pingsheng
Abstract: Steroid hormones play essential roles for living organisms. It has been long and well established that the endoplasmic reticulum (ER) and mitochondria are essential sites for steroid hormone biosynthesis because several steroidogenic enzymes are located in these organelles. The adrenal gland lipid droplet (LD) proteomes from human, macaque monkey, and rodent are analyzed, revealing that steroidogenic enzymes are also present in abundance on LDs. The enzymes found include 3β‐hydroxysteroid dehydrogenase (HSD3B) and estradiol 17β‐dehydrogenase 11 (HSD17B11). Analyses by Western blot and subcellular localization consistently demonstrate that HSD3B2 is localized on LDs. Furthermore, in vitro experiments confirm that the isolated LDs from HeLa cell stably expressing HSD3B2 or from rat adrenal glands have the capacity to convert pregnenolone to progesterone. Collectively, these data suggest that LDs may be important sites of steroid hormone metabolism. These findings may bring novel insights into the biosynthesis and metabolism of steroid hormones and the development of treatments for adrenal disorders.